GAYA BAHASA PADA IKLAN WEBSITE BIRO PERJALANAN WISATA JEPANG DI BALI - I Gede Arya Lanang; Ni Wayan Meidariani (SPHOTA: Jurnal Linguistik dan Sastra, 2020)
This paper discusses about the language style of advertising on Japanese website travel agents in Bali such as 1) www.charterbali.com 2) www.bali-guide.jp 3) www.balinavi.jp 4) www.oji-baliclub. com 5) www.bali-chili.com 6) www.dakadibali.com. The purpose of this study is to determine what kinds of language style are used in these advertisements. This research make use of Gorys Keraf’s theory on language style. The data in this study were obtained from six Japanese-language travel agents in Bali. The research method in this paper is a qualitative descriptive method. The language styles studied are those styles based on sentence structures. Based on sentence structures, eleven data have been found. They are five climax language styles, one anticlimax style, one data is antithesis language style, one data is parallelism language style, and two data are those typical of repetition language styles. The language styles found on the website are aim to convince Japanese tourists about the products on the website by repeating parts of words that are considered important, displaying important information at the beginning or the end of website.